2011
DOI: 10.1021/ja108698s
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Synthesis of Hierarchical Zeolite Beta via Network Formation of Uniform Nanocrystals

Abstract: A hierarchical mesoporous network of zeolite beta with very high micropore as well as mesopore volume was synthesized without the need of a porogen at near 100% yield in the form of easily retrievable micrometer-sized particles. This was achieved by a dense-gel synthesis utilizing steam-assisted conversion (SAC) to induce a burst of nucleation. During the first phase of the synthesis, individual, evenly sized zeolite beta nanoparticles are formed that subsequently condense into a porous network displaying unif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
166
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(184 citation statements)
references
References 54 publications
9
166
0
4
Order By: Relevance
“…Larger hysteresis loop occurs after p/p 0 & 0.45 in the adsorption-desorption isotherm of NZSM-5, which indicates not only the presence of mesopores but also a broad pore size distribution. Moreover, significant increase in N 2 adsorption is also observed, from p/p 0 & 0.8, for NZSM-5 because of the capillary condensation [3,7,8,25] in open mesopores or macropores obtained by filling the nano-rodlike MFI zeolite interparticles spaces. The pore size distribution derived from the adsorption branch of the isotherms (Fig.…”
Section: Synthesis and Characterizationmentioning
confidence: 94%
See 2 more Smart Citations
“…Larger hysteresis loop occurs after p/p 0 & 0.45 in the adsorption-desorption isotherm of NZSM-5, which indicates not only the presence of mesopores but also a broad pore size distribution. Moreover, significant increase in N 2 adsorption is also observed, from p/p 0 & 0.8, for NZSM-5 because of the capillary condensation [3,7,8,25] in open mesopores or macropores obtained by filling the nano-rodlike MFI zeolite interparticles spaces. The pore size distribution derived from the adsorption branch of the isotherms (Fig.…”
Section: Synthesis and Characterizationmentioning
confidence: 94%
“…Consequently, to improve the transport of molecules in microporous crystals is attracting significant research interests [3][4][5][6]. For a given material, the basic strategy to better the diffusion is to broaden the pore diameter or to shorten the diffusion path length [3][4][5][6][7][8][9][10][11]. To zeolites, enhancing the diffusion rate can be attained by decreasing the crystal size [7,8] or by introducing an additional meso-or/and macro-pore system into the individual zeolite crystal [3][4][5][6]9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, we show that mesoporous zeolite (ZSM-5, ZSM-12 and so on) with intercrystalline mesopore structure can be obtained through crystallization kinetics control, for instance, increasing super-saturation degree [31]. Very recently, Moller et al reported that hierarchical zeolite beta can be synthesized in one-step through network formation of uniform nanocrystals [32]. Such secondary template and post-treatment free mesoporous zeolite synthesis route allows mesoporous zeolites to be synthesized with a cost similar to or even lower than that of conventional zeolites and thus possibly opens a new, cost-effective, and industrially applicable way to the synthesis of mesoporous zeolites.…”
Section: Introductionmentioning
confidence: 94%
“…As mentioned before, DGC has been recognized as an effective way to introduce mesoporosity and reduce the crystal sizes [23,25,26]. Particularly, in the case of SAPO-34, major attention is focused on the understanding of condition-dependent formation mechanism at the molecular level.…”
Section: Introductionmentioning
confidence: 99%